PECULIARITIES OF INNOVATIVE STYLE OF TEACHER'S ACTIVITY IN CONDITIONS OF MODERNIZATION OF PEDAGOGICAL EDUCATION (Pedagogy of Higher and Secondary Education, 2022)
The article explains the mearing of notion «innovative teacher's activity, n do the structure and displays the level of professional activity of future primary school teachers. At chcidates, the pedagogical conditions of effective formation of innovative teacher's so in the process of their professional activity.
Keywords: innovation; innovate style of activity; motivational cognitive; creative and reflexive components; a future teacher